2017
DOI: 10.1038/s41598-017-03390-9
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant plasticity of peripheral sensory axons in a painful neuropathy

Abstract: Neuronal cells express considerable plasticity responding to environmental cues, in part, through subcellular mRNA regulation. Here we report on the extensive changes in distribution of mRNAs in the cell body and axon compartments of peripheral sensory neurons and the 3′ untranslated region (3′UTR) landscapes after unilateral sciatic nerve entrapment (SNE) injury in rats. Neuronal cells dissociated from SNE-injured and contralateral L4 and L5 dorsal root ganglia were cultured in a compartmentalized system. Axo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 82 publications
1
32
0
Order By: Relevance
“…Enrichment of mRNAs coding for protein synthesis, mitochondria, extracellular matrix, growth signals, peroxidase family, and the use of alternative long of 3 0 UTRs were also recently observed in preinjured axons of rat dorsal root ganglia (Hirai et al, 2017). Importantly, 3 0 UTR lengthening was reported for voltage-gated sodium channel NaV1.8, including alternative cleavage and polyadenylation, which may provide a novel mechanism to control the abundance of ion channels in neuropathic pain (Hirai et al, 2017). Thus, reproducible identification of transcript families for transmembrane proteins supports the contribution of the axonal ER biosynthetic machinery during development or damage.…”
Section: Biosynthesismentioning
confidence: 78%
See 1 more Smart Citation
“…Enrichment of mRNAs coding for protein synthesis, mitochondria, extracellular matrix, growth signals, peroxidase family, and the use of alternative long of 3 0 UTRs were also recently observed in preinjured axons of rat dorsal root ganglia (Hirai et al, 2017). Importantly, 3 0 UTR lengthening was reported for voltage-gated sodium channel NaV1.8, including alternative cleavage and polyadenylation, which may provide a novel mechanism to control the abundance of ion channels in neuropathic pain (Hirai et al, 2017). Thus, reproducible identification of transcript families for transmembrane proteins supports the contribution of the axonal ER biosynthetic machinery during development or damage.…”
Section: Biosynthesismentioning
confidence: 78%
“…In addition, roundabout homolog 1 (ROBO1), a guidance receptor relevant for development, as well as potassium/sodium hyperpolarization-activated cyclic nucleotide-gated ion channel (HCN2) and potassium voltage-gated channel subfamily A member 2 (KCNA2) have also been found in a pure axonal screen (Taylor et al, 2009). Enrichment of mRNAs coding for protein synthesis, mitochondria, extracellular matrix, growth signals, peroxidase family, and the use of alternative long of 3 0 UTRs were also recently observed in preinjured axons of rat dorsal root ganglia (Hirai et al, 2017). Importantly, 3 0 UTR lengthening was reported for voltage-gated sodium channel NaV1.8, including alternative cleavage and polyadenylation, which may provide a novel mechanism to control the abundance of ion channels in neuropathic pain (Hirai et al, 2017).…”
Section: Biosynthesismentioning
confidence: 90%
“…A solution that has emerged to solve this biological riddle is localized translation at nociceptor endings and/or along injured axons to control changes in gene expression. This solution is important because: (i) it explains how many endogenous pain-promoting molecules induce long-lasting plasticity [110]; (ii) it is supported by findings from experimental pain models in humans that are best explained by localized translation regulation [11,12]; and (iii) it provides insight into the generation of ectopic activity after peripheral nerve injury [6,1316], which is a major driver of neuropathic pain . In this review, we summarize rapidly growing, recent literature that elucidates the intricacies of translational control in persistent pain and highlight new therapeutic opportunities.…”
Section: Why Is Translational Control Important For Persistent Pain?mentioning
confidence: 99%
“…Nevertheless, several mRNAs have been localized to DRG axons in mice and rats, and some of these have been linked to pain hypersensitivity, such as the mRNAs for CREB, CPEB, and Na v 1.8 [38,39] (Table 2). Recent findings have also demonstrated that many other ion channel mRNAs localize to DRG axons and that the machinery needed to traffic these complex transmembrane proteins is also found in axons [13,16]. The development of genetic techniques for tagging ribosomes translating ribosome affinity purification (TRAP)] [40] in specific cellular populations will likely lead to important breakthroughs in our understanding of which mRNAs are translated locally in nociceptor axons to modulate excitability in response to injury.…”
Section: Local Mrna Translationmentioning
confidence: 99%
“…Despite the widespread use of this model system [35], many investigators are skeptical of the degree to which these cells in dissociated culture accurately reflect the status of nociceptors in vivo . Several studies have analyzed the genome wide RNA profiles of these cultures [25; 43], but not in the context of changes with respect to the intact ganglia. A previous study by Thakur et al [54] contrasted RNA sequencing (RNA-seq) profiles of intact DRGs with unsorted, dissociated DRGs in the context of profiling magnetically sorted, neuronally enriched dissociated DRGs.…”
Section: Introductionmentioning
confidence: 99%